Tumpang Tindih (Overlapping) Wanprestasi dan Penipuan Pidana dalam Penyelesaian Masalah Kontrak Komersial - Suwarti Suwarti; Wahda Z. Imam (Syntax Idea)
This research aims to analyze fraud in depth based on Article 1328 of the Civil Code in agreements that may result in breach of contract, as well as to examine the legal implications of commercial contracts containing elements of fraud based on Article 1328 of the Civil Code, where fraud can be annulled or declared void ab initio. The method used in this research is normative research on legal principles contained in Article 1328 of the Civil Code. The data used in this research are secondary data. The secondary data used in this research consist of primary legal materials that are authoritative, meaning they have authority, secondary legal materials, and tertiary legal materials. The research results show that fraud based on Article 1328 of the Civil Code in agreements does not result in breach of contract. This is because breach of contract and fraud in civil law have different elements. Breach of contract is regulated in Article 1243 of the Civil Code, while fraud in civil law is regulated in Article 1328 of the Civil Code. Breach of contract (negligence or inadvertence) by a party can take four forms: First, not doing what was promised to be done; Second, performing what was promised but not as promised; Third, performing what was promised but late; Fourth, doing something that, according to the agreement, should not be done. Meanwhile, fraud, as referred to in this research, consists of the concept of fraud found in Article 1328 of the Civil Code, namely, the presence of defects in will. Defects in will are caused by: mistake or negligence, coercion, and fraud. Therefore, to determine when breach of contract occurs and when fraud occurs depends on a person's intention. If there was already a malicious intent before the contract was closed/signed, then this constitutes an act of fraud. If a person's malicious intent arises after the contract is closed/signed, then this is an act of breach of contract.